Accountancy students’ and lecturers’ perceptions of the effect of open-book assessments on writing examinations - Kruger, S.J. (South African Journal of Higher Education, 2020)
Open-book assessment (OBA) can contribute to the development of competency in handling large amounts of information in the knowledge economy. This is one of the reasons why the South African Institute of Chartered Accountants (SAICA) implemented OBA for its Initial Test of Competence. This empirical study investigated final year accountancy students’ and lecturers’ perceptions of the effect on writing examinations after their method of assessment changed from a closed-book (CBA) to an open-book assessment format. Students and lecturers perceived a change in writing behaviour, reduced anxiety, and improved performance. On some aspects the level of agreement between students and lecturers differed significantly. There is also evidence that African students perceived OBA to be less beneficial compared to the perceptions of white students. For subjects for which substantial texts were available, students perceived the least change happened for Auditing while lecturers perceived the least change for Financial Accounting. Both students and lecturers perceived the most change happened for Taxation. It is important that lecturers at departments of accountancy take cognisance of these perception gaps and to adjust their teaching to enable their students to utilise their texts as an additional resource optimally. This study is also of value to the regulatory bodies to evaluate their assessment practises.